A three-dimensional left atrial motion estimation from retrospective gated computed tomography: application in heart failure patients with atrial fibrillation - Sillett, Charles; Razeghi, Orod; Lee, Angela W. C.; Solis Lemus, Jose Alonso; Roney, Caroline; Mannina, Carlo; de Vere, Felicity; Ananthan, Kiruthika; Ennis, Daniel B.; Haberland, Ulrike; Xu, Hao; Young, Alistair; et al. (Frontiers in Cardiovascular Medicine, 2024)
Reduced left atrial (LA) strain correlates with atrial fibrillation (AF) presence. Conventional atrial strain analysis uses two-dimensional (2D) imaging which is limited by atrial foreshortening and underestimation of through-plane motion. Retrospective gated computed tomography (RGCT) produces high fidelity three-dimensional (3D) images of the cardiac anatomy throughout the cardiac cycle which can be used for 3D mechanics estimation. Its feasibility for LA strain measurement however is understudied. The aim of this study is to develop and apply a novel workflow to estimate 3D LA motion and calculate strain from RGCT imaging. The utility of global and regional strain to separate heart failure with reduced ejection fraction (HFrEF) patients with and without AF is investigated. A cohort of thirty HFrEF patients with (n=9) and without (n=21) AF underwent RGCT prior to cardiac resynchronization therapy. The temporal sparse free form deformation (TSFFD) image registration method was optimised for LA feature tracking in RGCT images and used to estimate 3D LA endocardial motion. Area and fibre reservoir strain was calculated over the LA body. Universal atrial coordinates and a human atrial fibre atlas enabled regional strain calculation and the fibre strain calculation along local myofibre orientation, respectively. Global reservoir strains were significantly reduced in the HFrEF+AF versus the HFrEF-only group (area strain: 11.2 ± 4.8% vs 25.3 ± 12.6%, p=0.001; fibre strain: 4.5 ± 2.0% vs 15.2 ± 8.8%, p=0.001) and HFrEF+AF patients had greater regional reservoir strain dyssynchrony. All regional reservoir strains were reduced in the HFrEF+AF group, where the inferior wall strains exhibited the most significant differences. Global reservoir fibre strain and LA volume + posterior wall reservoir fibre strain outperformed LA volume alone and 2D global longitudinal strain (GLS) for AF classification (area-under-the-curve: global reservoir fibre strain: 0.94 ± 0.02, LA volume + posterior wall reservoir fibre strain: 0.95 ± 0.02, LA volume: 0.89 ± 0.03, 2D GLS: 0.90 ± 0.03). RGCT enables 3D LA motion estimation and strain calculation which outperforms 2D strain metrics and LA enlargement for AF classification. Differences in regional LA strain could reflect regional myocardial properties, such as atrial fibrosis burden.